Misconception Analysis of Cell Material Using Four-Tier Multiple Choice Diagnostic Test - Naufal Ahmad Muzakki; Sariwulan Diana; Didik Priyandoko (Program Studi Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kuningan, 2023)
The purpose of students learning biology is to understand the concepts in biology, be able to connect one concept to another, and apply the learned concepts in daily life. Inability to properly connect concepts may cause misconceptions that will affect students' achievement. Therefore, the purpose of this study is to analyze students' misconceptions on the topic of cells using a four-tier multiple choice diagnostic test. The research method used is research and development. The subjects in this study were 36 students of class XI science at SMA Muhammadiyah 5 Rancaekek. The results of developing a diagnostic test using the content validity ratio (CVR) method produced a CVR value of 0.75 (CVR ≥ 0.672) and the content validity index (CVI) method produced a value of 0.87 so that the developed diagnostic test was feasible to use. The results of the analysis of misconceptions experienced by students showed that on the topic of chemical components making up cells 10.42%, cell structure 10.42%, cell function 13.89%, differences between animal and plant cells 17.36%, and bio-processes in cells 11.81%. Overall, the misconceptions experienced by students regarding cell material were 12.78% (misconceptions > 10%), which means that a misconception experienced by students was considered significant.